Evaluation of a pumping test with skin effect and wellbore storage on a confined aquifer in the Bela Crkva, Serbia. (2019) - Holub, Jiri; Pech, Pavel; Kuraz, Michal; Maca, Petr; Kahuda, Daniel
Pumping test is a fundamental method to determinate aquifer hydraulic parameters. The main evaluated hydraulic parameters are the transmissivity and the aquifer storage coefficient. For estimation of these parameters a semi-logarithmic straight line method is commonly used, which is based on the assumptions of the Theis mathematical model. Nevertheless, there are other parameters corresponding to real conditions during the pumping test, such as the skin effect and the wellbore storage. The evaluation of pumping test data is usually carried out by estimation through curve matching a straight line to drawdown data plotted on a semi-log graph. Neglecting the skin effect and the wellbore storage can lead to false analysis of the time-drawdown variation in the pumping well. Here an evaluation method is developed to estimate the transmissivity, the aquifer storage coefficient, skin effect and wellbore storage from the pumping test data showing this characteristic curve shape.